Le Wessex, espace étranger - Isabelle Gadoin-Luis (Cahiers Victoriens et Edouardiens)
It is now well agreed that far from being the comfortable reproduction of the picturesque counties of Hardy’s native Dorset, Wessex is a territory of the imagination, a territory that evolves along with the novels, to finally appear in all its unfathomable scope and distance at the end of the work. This paper offers a phenomenological interpretation of two key-scenes at the end of Tess of the d’Urbervilles, when Tess and Angel at Flintcomb-Ash then at Stonehenge are progressively alienated from their living world, barred from any form of communion or intimacy with it, and made to realise the insignificance and powerlessness of any rational subject when faced with the raw, primordial forces of nature. As the horizon of the known world suddenly seems to retreat away from the protagonists, inaccessible, frightening backgrounds are fleetingly revealed, and Wessex acquires a dimension that might well be called transcendent, not in any religious sense, far from it — but in the sense of what escapes and resists man’s powers of apprehension, representation and rational knowledge or mastery. But while it defeats any form of intentionality, this « other » world does offer itself to those who, like Tess, trust in mere sense — perceptions, and define themselves through their perceptual contact with the world. The evolution of Wessex thus allows us to redefine the traditional concepts of subject and object : from rational subject to being-in-the-world, from external nature to field of perceptions.